Effect of cis-platinum(II)diamminodichloride on cell division of Hyphomicrobium and Caulobacter. - Moore, R L (1976)
Low concentrations of the radiomimetic agent cis-platinum(II)diamminodichloride (PDD) inhibited cell division in Caulobacter crescentus (0.1 mug/ml) and Hyphomicrobium sp. strain B-522 (1.0 mug/ml) without altering the length of prosthecae. After exposure, cells of C. crescentus appeared as long filaments, whereas only the bud portion of Hyphomicrobium underwent elongation. PDD-treated cells of both species were multinucleated. After the removal of PDD by washing, filaments of C. crescentus fragmented unequally and then normal growth resumed. In Hyphomicrobium (where division involves release of swarmer cells that arise as buds on the distal ends of hyphae), potential septation sites formed in the presence of PDD remained inactive after washing. Reinitiation of cell division in this species was dependent upon the synthesis of new hyphae that could arise from either end of the elongated bud. This finding suggests that the PDD-induced lesion at a given septation site is irreversible and, upon removal of this compound, alternate sites must be synthesized for the subsequent occurrence of cell division.